A Systematic Review Exploring the Economic Valuation of Accessing and Using Green and Blue Spaces to Improve Public Health - Mary Lynch (International Journal of Environmental Research and Public Health, 2020)
Contact with the natural environment in green and blue spaces can have a valuable influence on population physical and mental health and wellbeing. The aim of this study is to explore the economic evidence associated with the public’s value for accessing, using and improving local environments to undertake recreational activity and consuming the associated health benefits of green and blue spaces. Applying the Preferred Reporting Items for Systemic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic literature search was conducted. Peer-reviewed articles were sought using electronic databases, scrutiny of reference lists, experts and grey literature. All relevant papers meeting the criteria were critically appraised for methodological quality using the Drummond checklist. The review search concluded with 12 papers applying the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach to assess the quality with a narrative analysis conducted under the themes. Results suggest the public value access to green and blue spaces to undertake recreational activities and avoid delay or losing the recreational experience and associated health benefits. The public are willing to pay between £5.72 and £15.64 in 2019 value estimates for not postponing or losing an outdoor experience and for walking in local environments under current and improved environmental conditions, respectively. Valuation estimates indicate the public value green and blue spaces and are willing to pay to improve local environments to gain the health benefits of undertaking leisure activities in green and blue spaces.